2004
DOI: 10.1149/1.1809586
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Calculations of Intermediates of Oxygen Reduction on Low-Index Platinum Surfaces

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
187
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(206 citation statements)
references
References 77 publications
17
187
0
1
Order By: Relevance
“…OH ads , rather than O ads , seems the likely next intermediate on the way to the final H 2 O product, as can be concluded, again, from the deep energy sink associated with O ads on Pt. The recent DFT calculations further support the O 2 -to-OOH ads -to-OH ads route by showing that OOH is indeed an intermediate of significant bonding energy to Pt, at least on some Pt crystal surfaces [Panchenko et al, 2004]. Another important contribution of the theoretical calculations has been in providing an explanation for the higher measured ORR activity of Pt-alloy catalysts versus unalloyed Pt.…”
Section: Electrocatalysis Of Oxygen Reduction In the Fuel Cell Cathodementioning
confidence: 84%
See 2 more Smart Citations
“…OH ads , rather than O ads , seems the likely next intermediate on the way to the final H 2 O product, as can be concluded, again, from the deep energy sink associated with O ads on Pt. The recent DFT calculations further support the O 2 -to-OOH ads -to-OH ads route by showing that OOH is indeed an intermediate of significant bonding energy to Pt, at least on some Pt crystal surfaces [Panchenko et al, 2004]. Another important contribution of the theoretical calculations has been in providing an explanation for the higher measured ORR activity of Pt-alloy catalysts versus unalloyed Pt.…”
Section: Electrocatalysis Of Oxygen Reduction In the Fuel Cell Cathodementioning
confidence: 84%
“…1.2) [Nørskov et al, 2004] (rather than a single metal atom or a pair of metal atoms as was done in pioneering contributions made somewhat earlier [Anderson et al, 2000]), as well as the aqueous molecular environment adjacent to the metal catalyst surface. Last, but not least, the effects of variations in the electrode-electrolyte potential difference on interfacial thermodynamics and dynamics have also been included in these models [Nørskov et al, 2004;Panchenko et al, 2004;Desai and Neurock, 2003]. Figure 1.2 Free energy map for the "associative mechanism" of ORR at Pt metal and the steps considered in this mechanism [Nørskov et al, 2004].…”
Section: Electrocatalysis Of Oxygen Reduction In the Fuel Cell Cathodmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of ORR on Pt 9 (111) concluded that the favorable position of oxygen adsorption were the hollow and bridge site [5]. Furthermore, the other previous calculation using a slab model also stated that O 2 molecule tended to be adsorbed on these two sites [18].…”
Section: B Effect Of Position and Orientation Of Adsorbed Omentioning
confidence: 91%
“…Although their work provided the useful results of the dissociative adsorption process considering the one-electron transfer, it was limited to describe the ionization potential (IP) and electron affinity (EA) Due to time-consuming computations for large-sized electronic structures, effectively smaller scale models are thus required for more improvements. Panchenko et al [5] carried out a density functional theory (DFT) calculation using a cluster model of Pt 9 (111) and showed the capability of computing the adsorption energy, geometry, and the charge transfer in such a small-scale system.…”
Section: Introductionmentioning
confidence: 99%